Knowledge Mapping of Drug Repositioning’s Theme and Development - Lang X; Liu J; Zhang G; Feng X; Dan W (Dove Medical Press, 2023)
Xiaona Lang,1 Jinlei Liu,2 Guangzhong Zhang,3 Xin Feng,1 Wenchao Dan3 1Pharmacy Department, Tianjin Hospital, Tianjin, People's Republic of China; 2Cardiology Department, Guang 'anmen Hospital, Chinese Academy of Traditional Chinese Medicine, Beijing, People's Republic of China; 3Dermatological Department, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Wenchao Dan, Dermatological Department, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People's Republic of China, Tel +86 13652001152, Email dan9521@foxmail.comBackground: In recent years, the emergence of new diseases and resistance to known diseases have led to increasing demand for new drugs. By means of bibliometric analysis, this paper studied the relevant articles on drug repositioning in recent years and analyzed the current research foci and trends.Methodology: The Web of Science database was searched to collect all relevant literature on drug repositioning from 2001 to 2022. These data were imported into CiteSpace and bibliometric online analysis platforms for bibliometric analysis. The processed data and visualized images predict the development trends in the research field.Results: The quality and quantity of articles published after 2011 have improved significantly, with 45 of them cited more than 100 times. Articles posted by journals from different countries have high citation values. Authors from other institutions have also collaborated to analyze drug rediscovery. Keywords found in the literature include molecular docking (N=223), virtual screening (N=170), drug discovery (N=126), machine learning (N=125), and drug-target interaction (N=68); these words represent the core content of drug repositioning.Conclusion: The key focus of drug research and development is related to the discovery of new indications for drugs. Researchers are starting to retarget drugs after analyzing online databases and clinical trials. More and more drugs are being targeted at other diseases to treat more patients, based on saving money and time. It is worth noting that researchers need more financial and technical support to complete drug development.Keywords: drug repositioning, drug discovery, bibliometric, citation analysis, trend analysis